High throughput sequencing analysis reveals amelioration of intestinal dysbiosis by squid ink polysaccharide - Shangyun Lu; Tao Zuo; Na Zhang; Hongjie Shi; Fang Liu; Juan Wu; Yuming Wang; Changhu Xue; Qing-juan Tang (Journal of Functional Foods, 2016)
Cyclophosphamide (Cy) is the most commonly used clinical chemotherapeutic drug for cancer treatment, although it damages the microbial ecology of the gut. This study focuses on the utilisation of food-derived functional components to manipulate the gut microbiota. With a mouse model injected with Cy, the protective effect of squid ink polysaccharide (SIP) on chemotherapy-induced intestinal dysbiosis was investigated by high-throughput sequencing. The shifts in relative abundance of the dominant taxa at the phylum, class, family, and genus levels show the incredible effects of SIP. In short, SIP decreases the abundance of Ruminococcus, Bilophila, Oscillospira, Dorea and, especially, Mucispirillum, which thrives in the early disruption of the colonic surface mucus layer and induces inflammatory disorders. Our results may have important implications for the use of SIP as a functional food component with potential therapeutic utility in manipulating the gut microbiota.